Kurze Bemerkungen zum baltischen und slawischen Modell der Seele Notes on the Baltic and Slavic Structure of the Soul - Gliwa, Bernd (Studia mythologica Slavica, 2007)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">A new etymology of Lithuanian sveikata ‘health’ is provided. The imperative *sueiki! ‘go together!’ developed regularly into sveiki! ‘be healthy!’ having the behaviour of an newly created adjective sveikas ‘complete, healthy’. Health results if the soul is fixed within the body. Therefore, Lithuanian siela ‘soul’ and the cognate Sl. *sila ‘force’ is related to I.-E. *seH-i- ‘to connect, bind’. This indicates the soul being well incorporated into the body and names the physical part of the soul, leading to health and strongness of a person.